Exports and invoicing: Evidence from the 2015 Swiss Franc appreciation - Raphael A. Auer; Ariel T. Burstein; Katharina Erhardt; Sarah M. Lein-Rupprecht (University of Basel, Center of Business and Economics (WWZ), 2020)
The Swiss National Bank's (SNB) elimination of the lower bound on the EUR/CHF exchange rate on January 15 2015 provides a unique setting to study how prices and quantities respond to changes in nominal exchange rates. In this paper, we complement the study of imports in Auer et al. (2020) by looking at how the response of Swiss export prices and export values varies across products according to the currency of invoicing at the border. The rate of pass through (measured in CHF) into export prices was much lower in industries with a higher share of CHF-invoiced export border prices. We show that industries with higher CHF-invoicing shares experienced substantially weaker export growth in the two-year period after January 2015. At short horizons, however, export quantities did not respond across industries as much as prices to the exchange rate shock.
Keywords: F11; F31; F41; L11; 330; Large exchange rate shocks; exchange rate pass-through; invoicing currency; expenditure switching; price-setting; nominal and real rigidities